Analysis of climate-driven processes in clayey slopes for early warning system design. Issue 6 (3rd May 2019) - Cotecchia, Federica; Tagarelli, Vito; Pedone, Giuseppe; Ruggieri, Gennaro; Guglielmi, Simona; Santaloia, Francesca
Abstract : The activity of deep landslides in slopes formed of clayey turbidites has been observed to be connected to the climatic regime in the Mediterranean, based on field data and phenomenological interpretations. With the aim of investigating this connection, the effects of the soil–vegetation–atmosphere interaction on the piezometric regime were investigated by means of hydraulic finite-element analyses of the transient seepage across a prototype clayey slope. The ground surface condition was defined accounting for rainfall and evapotranspiration flux, estimated through the United Nations' Food and Agriculture Organization Penman–Monteith approach. The predicted excursions of the piezometric head within the slope over time were found to agree with field observations. The predicted piezometric profiles were investigated to evaluate the infiltration processes during the year and show how these bring about seasonal piezometric excursions. The results of the hydraulic analyses were then input into limit equilibrium analyses to assess the impact of the slope–vegetation–atmosphere interaction on the stability of landslide bodies of different depths. The results show how such impact depends on the stratigraphy of the slope. Furthermore, the variability of the climatic precursor of landsliding with landslide depth was characterised to guide the design of early warning systems for mitigation purposes.